High-thermal-conductivity aluminum-based copper-clad plate and preparation method thereof
By setting a resin adhesive layer and a thermally conductive adhesive layer in the aluminum-based copper clad laminate, and filling the thermally conductive adhesive layer with thermally conductive filler, the problems of insufficient adhesion and thermal conductivity of the aluminum-based copper clad laminate are solved, achieving the effect of high thermal conductivity and high peel strength.
Patent Information
- Application Number
- CN202511941643.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-03-20
AI Technical Summary
The insulation layer of existing aluminum-based copper clad laminates has a high content of inorganic fillers, which leads to poor adhesion between the insulation layer and the copper foil, reduced peel strength, and insufficient thermal conductivity.
The method involves setting a first resin adhesive layer between an aluminum substrate and a thermally conductive adhesive layer, and setting a second resin adhesive layer between a copper foil and a thermally conductive adhesive layer. The thermally conductive adhesive layer is filled with thermally conductive fillers such as alumina, boron nitride, and silicon carbide. The resin adhesive layer and the thermally conductive adhesive layer are formed with uniform thickness through methods such as micro-gravure coating and slit coating, combined with a hot-pressing composite process.
A thermal conductivity of 5.9 W/(m・K) and a peel strength of ≥1.2 N/mm were achieved, significantly improving the thermal conductivity and adhesion of aluminum-based copper clad laminates.
Smart Images

Figure CN121697284A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic packaging materials technology, specifically to a high thermal conductivity aluminum-based copper clad laminate and its preparation method. Background Technology
[0002] Aluminum-based copper clad laminate (CCL) is a layered composite material formed by a composite process of an aluminum substrate, an insulating and thermally conductive layer, and copper foil. Due to the excellent heat dissipation performance of the aluminum substrate, the good conductivity of the copper foil, and the electrical isolation provided by the insulating layer, it has become a core packaging material for high-power electronic devices (such as LED lighting modules, new energy vehicle power controllers, and 5G base station power modules). Its core performance indicators are mainly reflected in thermal conductivity (which determines heat dissipation efficiency and must be ≥3.5W / (m・K) to meet the heat dissipation requirements of high-power devices) and interlayer adhesion (measured by peel strength and must be ≥1.2N / mm to ensure structural stability during long-term use and avoid device failure caused by interlayer peeling).
[0003] However, the high content of inorganic fillers in the insulating and thermally conductive resin layer of existing aluminum-based copper clad laminates leads to poor adhesion between the insulation layer and the copper foil, resulting in a decrease in the peel strength of the aluminum-based copper clad laminate.
[0004] Existing technology CN111823693A provides a method for preparing a high thermal conductivity copper-clad laminate. This method involves adding a high content of inorganic filler to the adhesive solution in two stages, and then using a two-coating method to coat two different adhesive solutions containing different inorganic fillers onto a copper foil to form an insulating layer, ensuring the thermal conductivity and peel strength of the high thermal conductivity copper-clad laminate. However, the thermal conductivity of the insulating layer in the high thermal conductivity copper-clad laminate of existing technology CN111823693A is only up to 2.1 W / (m·K).
[0005] Existing technology CN 104708869 A provides a high thermal conductivity aluminum-based copper clad laminate and its manufacturing method. This involves filling a high thermal conductivity insulating layer with alumina fibers, which are produced by micro-arc oxidation. The alumina content in the alumina fibers accounts for 10-80% of the weight of the high thermal conductivity insulating layer. The fiber diameter of the alumina fibers is 0.1-200 μm, and the aspect ratio of the alumina fibers is 1:1-2000:1. Existing technology CN 104708869 A describes that the high thermal conductivity insulating layer improves lateral heat dissipation capacity and heat dissipation effect, resulting in a high thermal conductivity insulating layer with excellent thermal conductivity, good toughness, and strong adhesion, thereby improving the reliability of metal-based copper clad laminates with this high thermal conductivity insulating layer material. However, it does not actually disclose the formula of the high thermal conductivity insulating layer, nor its thermal conductivity properties and peel strength. Summary of the Invention
[0006] To address the aforementioned problems, this invention provides a high thermal conductivity aluminum-based copper clad laminate and its preparation method, achieving a thermal conductivity of 5.9 W / (m・K) and a peel strength ≥1.2 N / mm.
[0007] The objective of this invention is achieved in the following manner: a high thermal conductivity aluminum-based copper clad laminate, comprising an aluminum substrate, a copper foil, and a thermally conductive adhesive layer located between the two, wherein a first resin adhesive layer is provided between the aluminum substrate and the thermally conductive adhesive layer, and a second resin adhesive layer is provided between the copper foil and the thermally conductive adhesive layer; the thicknesses of the first resin adhesive layer and the second resin adhesive layer are 5-10 μm, respectively; the filling amount of thermally conductive filler in the thermally conductive adhesive layer is approximately 70%-85% of the resin volume in the thermally conductive adhesive layer, the resin of the thermally conductive adhesive layer is epoxy resin and phenolic resin, and the resins of the first resin adhesive layer and the second resin adhesive layer are at least one of epoxy resin and phenolic resin.
[0008] The resin matrix system of the thermally conductive adhesive layer comprises: 50-60 parts epoxy resin, 40-50 parts phenolic resin, and 3-10 parts curing agent; the thermally conductive filler is selected from at least one of alumina, boron nitride, silicon carbide, and diamond, with a particle size of 1-50 μm. The thermally conductive filler has a composite particle size distribution, wherein 1-10 μm particles account for 30-40%, 10-30 μm particles account for 40%-50%, and 30-50 μm particles account for 10%-20%.
[0009] The thickness of the thermally conductive adhesive layer is 130~180mm.
[0010] The raw materials for the first resin adhesive layer and the second resin adhesive layer respectively include 2-5 parts of resin and 0.3 parts of curing agent.
[0011] The preparation method of the aluminum-based copper-clad laminate includes the following steps: (1) Add all raw materials except curing agent to the mixing equipment for the first resin adhesive layer, the second resin adhesive layer and the thermally conductive adhesive layer and mix them evenly. Then add curing agent and continue to mix evenly to obtain the coating liquids of the first resin adhesive layer, the second resin adhesive layer and the thermally conductive adhesive layer respectively. (2) A coating liquid for coating the first resin adhesive layer is applied to one side of the aluminum substrate and pre-cured to form the first resin adhesive layer; (3) Apply a coating liquid of thermally conductive adhesive layer to the surface of the first resin adhesive layer and pre-cur it to form a thermally conductive adhesive layer; (4) The coating liquid of the second resin adhesive layer is applied to the thermally conductive adhesive layer and then hot-pressed with the roughened copper foil; or the coating liquid of the second resin adhesive layer is directly applied to the roughened surface of the copper foil to form the second resin adhesive layer, and then pressed with the aluminum substrate that has been coated with the thermally conductive adhesive layer.
[0012] The coating liquids of the first resin adhesive layer, the second resin adhesive layer, and the thermally conductive adhesive layer are applied by micro-recessed coating, slot coating, or wire rod coating. The wet film thickness is controlled to be 8~15μm, and the dry film thickness after pre-curing is 5~10μm.
[0013] The solvent is methyl ethyl ketone.
[0014] Compared with the prior art, the present invention provides a high thermal conductivity aluminum-based copper clad laminate and its preparation method, with a thermal conductivity of 5.9 W / (m・K) and a peel strength ≥1.2 N / mm. Attached Figure Description
[0015] Figure 1 This is a schematic diagram of the structure of the high thermal conductivity aluminum-based copper-clad laminate of the present invention.
[0016] Wherein, 1-aluminum substrate, 2-first resin adhesive layer, 3-thermal conductive adhesive layer, 4-second resin adhesive layer, 5-copper foil. Detailed Implementation
[0017] like Figure 1 As shown, a high thermal conductivity aluminum-based copper clad laminate includes an aluminum substrate 1, a copper foil 5, and a thermally conductive adhesive layer 3 located between the two. A first resin adhesive layer 2 is provided between the aluminum substrate 1 and the thermally conductive adhesive layer 3, and a second resin adhesive layer 4 is provided between the copper foil 5 and the thermally conductive adhesive layer 3. The thicknesses of the first resin adhesive layer and the second resin adhesive layer are 5-10 μm, respectively. The filling amount of thermally conductive filler in the thermally conductive adhesive layer is about 70%-85% of the resin volume in the thermally conductive adhesive layer. The resin of the thermally conductive adhesive layer is epoxy resin and phenolic resin, and the resins of the first resin adhesive layer and the second resin adhesive layer are at least one of epoxy resin and phenolic resin.
[0018] The raw materials of the resin matrix system of the thermally conductive adhesive layer are: 50-60 parts of epoxy resin, 40-50 parts of phenolic resin, and 3-10 parts of curing agent; the thermally conductive filler is selected from at least one of alumina, boron nitride, silicon carbide, and diamond, and its particle size is 1-50 μm.
[0019] The thermally conductive filler has a composite particle size distribution, in which 1-10μm particles account for 30-40%, 10-30μm particles account for 40%-50%, and 30-50μm particles account for 10%-20%.
[0020] The thickness of the thermally conductive adhesive layer is 130~180mm.
[0021] The raw materials in the first resin adhesive layer and the second resin adhesive layer respectively include 2-5 parts of resin and 0.3 parts of curing agent.
[0022] To ensure uniform mixing and easy coating of the raw materials for the first resin adhesive layer, the second resin adhesive layer, and the thermally conductive adhesive layer, a solvent is used to dissolve or disperse these materials. The solvent evaporates during the drying process after coating. The amount of solvent in the thermally conductive adhesive layer can be 40-50 parts; the amount of solvent in the first and second resin adhesive layers is 15-20 parts each. The solvent can be methyl ethyl ketone.
[0023] The preparation method of the aluminum-based copper-clad laminate includes the following steps: (1) Add all raw materials and solvents except curing agent to the raw materials of the first resin adhesive layer, the second resin adhesive layer and the thermally conductive adhesive layer and mix them evenly in a mixing device. Then add curing agent and continue to mix evenly to obtain coating liquids of the first resin adhesive layer, the second resin adhesive layer and the thermally conductive adhesive layer respectively. (2) A coating liquid for coating the first resin adhesive layer is applied to one side of the aluminum substrate and pre-cured to form the first resin adhesive layer; (3) Apply a coating liquid of thermally conductive adhesive layer to the surface of the first resin adhesive layer and pre-cur it to form a thermally conductive adhesive layer; (4) The coating liquid of the second resin adhesive layer is applied to the thermally conductive adhesive layer and then hot-pressed with the roughened copper foil; or the coating liquid of the second resin adhesive layer is directly applied to the roughened surface of the copper foil to form the second resin adhesive layer, and then pressed with the aluminum substrate that has been coated with the thermally conductive adhesive layer.
[0024] The coating liquids of the first resin adhesive layer, the second resin adhesive layer, and the thermally conductive adhesive layer are applied by micro-recessed coating, slot coating, or wire rod coating. The wet film thickness is controlled to be 8~15μm, and the dry film thickness after pre-curing is 5~10μm.
[0025] The present invention will now be described in detail with reference to specific embodiments. It should be noted that these embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above description of the present invention.
[0026] The raw materials used in this invention are sourced as follows: epoxy resin: trade name "Epicoto 828US", manufactured by Mitsubishi Chemical Co., Ltd.; N-methylimidazolium curing agent: from Shanghai Rongli Chemical Technology Co., Ltd.; phenolic resin: trade name PR12603, from Sumitomo Bakelite Co., Ltd., Japan; thermally conductive filler: alumina particles, from Dongguan Dongchao New Materials Co., Ltd.; solvent: methyl ethyl ketone (MEK), a commercially available product.
[0027] Example 1 A method for preparing a high thermal conductivity aluminum-based copper-clad laminate. 1.1 Raw material formulation The raw materials for the first resin adhesive layer and the second resin adhesive layer are: 0.3g epoxy resin, 0.2g phenolic resin, 1.5g solvent MEK, and 0.03g curing agent N-methylimidazole. The raw materials for the thermally conductive adhesive layer are: 5 g epoxy resin; 5 g phenolic resin; 0.3 g N-methylimidazole curing agent; 4 g MEK solvent; and Al2O3 thermally conductive filler, in graded proportions: 3.9 g for 1~10 μm specification, 15.6 g for 10~30 μm specification, and 6.8 g for 30~50 μm specification. Note: The total filling amount of thermally conductive filler is 70% of the resin volume in the thermally conductive adhesive layer. The density of epoxy resin and phenolic resin is calculated as 1 g / cm³. 3 The density of Al2O3 is calculated to be 3.9 g / cm³. 3 calculate.
[0028] 1.2 Preparation steps Step A: Preparation and pre-curing of the first resin adhesive layer All raw materials of the first resin adhesive layer, except for the curing agent, are added to a mixing device and stirred for 30 minutes until homogeneous. After adding the curing agent, stirring is continued for 30 minutes to obtain the coating liquid of the first resin adhesive layer. The coating liquid of the first resin adhesive layer was applied to the surface of the aluminum plate substrate by using a wire rod, and dried and pre-cured at 120°C for 5 minutes to obtain a thickness of 6μm for the first resin adhesive layer. Step B: Coating and drying of thermally conductive adhesive layer Add all the raw materials of the thermally conductive adhesive layer except the curing agent to the mixing equipment and stir for 30 minutes until uniform; after adding the curing agent, continue stirring for 30 minutes to obtain the coating liquid of the thermally conductive adhesive layer; The coating liquid of the thermally conductive adhesive layer is coated on the surface of the first resin adhesive layer prepared in step A. It is first dried at 120°C for 10 min, and then heated to 150°C and held for 5 min. The thickness of the obtained thermally conductive adhesive layer is 150 μm. Step C: Application of the second resin adhesive layer Using the same raw material formulation and coating and pre-curing process as in step A, a second resin adhesive layer is coated on the surface of the thermally conductive adhesive layer to obtain a second resin adhesive layer with a thickness of 6 μm. Step D: Hot pressing composite molding Copper foil is covered on the other side of the second resin adhesive layer (ensuring the roughened side of the copper foil faces down), and hot-pressed for 240 minutes at 90~170℃ and 10MPa (initial temperature is 90℃, and the temperature is increased to 170℃ at a heating rate of 2℃ / min). After cooling, the finished aluminum-based copper-clad laminate is obtained.
[0029] 1.3 Performance Test Results Thermal conductivity: 5.9 W / (m·K); Copper foil peel strength: 1.4 N / mm.
[0030] Example 2: Comparison of resin-free adhesive layer schemes 2.1 Variable Design The first and second resin adhesive layers were removed, and the raw materials of the first and second resin adhesive layers in Example 1 were directly added to the resin matrix raw material of the thermally conductive adhesive layer. The formulation of the remaining raw materials (including the thermally conductive filler ratio) was completely consistent with that of Example 1. The total filling amount of the thermally conductive filler became 66.7% of the resin volume in the thermally conductive adhesive layer.
[0031] 2.2 Preparation process (A) Coating and drying of thermally conductive adhesive layer All raw materials except the curing agent in the above thermally conductive adhesive layer raw materials are added to a mixing device and stirred for 30 minutes until homogeneous; after adding the curing agent, stirring is continued for 30 minutes to obtain the coating liquid of the thermally conductive adhesive layer. The coating liquid for applying a thermally conductive adhesive layer to the surface of an aluminum plate was first dried at 120°C for 10 minutes, and then heated to 150°C and held for 5 minutes, resulting in a thermally conductive adhesive layer thickness of 159 μm. (B) Hot pressing composite molding Cover the other side of the thermally conductive adhesive layer with copper foil (ensure the roughened side of the copper foil faces down), and hot press for 240 min at 90~170℃ and 10MPa (heating rate 2℃ / min). After cooling, the finished aluminum-based copper-clad laminate is obtained.
[0032] Except for the absence of the first and second resin adhesive layer coating steps, the other process parameters (stirring time, drying temperature / time, hot pressing conditions, etc.) are exactly the same as in Example 1. 2.3 Performance Test Results and Analysis Thermal conductivity: 5.6 W / (m·K) (5.1% lower than Example 1); Copper foil peel strength: 0.8 N / mm (42.9% lower than in Example 1); Conclusion: Without the first and second resin adhesive layers, the adhesion of the aluminum-based copper clad laminate decreased significantly, and the thermal conductivity also decreased compared to Example 1. This indicates that directly adding the raw materials of the first and second resin adhesive layers to the resin matrix of the thermally conductive adhesive layer not only fails to improve the peel strength but also reduces the thermal conductivity. This proves that the first and second resin adhesive layers of this application improve the adhesion while ensuring the high thermal conductivity of the aluminum-based copper clad laminate. Example 3 A method for preparing a high thermal conductivity aluminum-based copper-clad laminate. 3.1 Variable Design The resin system formulation (including curing agent and solvent ratio) of the first resin adhesive layer, the second resin adhesive layer, and the thermally conductive adhesive layer is completely consistent with that of Example 1; only the graded ratio of thermally conductive filler (Al2O3) in the thermally conductive adhesive layer is adjusted: 3.9g for 1-10μm specification, 17.55g for 10-30μm specification, and 7.8g for 30-50μm specification; so that the total filling amount of thermally conductive filler is increased to 75% of the resin volume in the thermally conductive adhesive layer; the thickness of the first resin adhesive layer and the second resin adhesive layer is 6μm.
[0033] 3.2 Preparation process Except for the thermally conductive filler ratio, the other process parameters (stirring time, drying / pre-curing conditions, hot pressing parameters, etc.) are exactly the same as in Example 1, wherein the thickness of the thermally conductive adhesive layer after drying is 155μm.
[0034] 3.3 Performance Test Results and Analysis Thermal conductivity: 6.2 W / (m·K) (5.1% improvement over Example 1); Copper foil peel strength: 1.3 N / mm (only 7.1% lower than in Example 1); Conclusion: By increasing the amount of thermally conductive filler and optimizing the proportion of medium-sized (10-30μm) Al2O3, the thermal conductivity can be significantly improved while slightly reducing the adhesion, thus achieving a performance balance. Example 4 4.1 Variable Design The resin system formulation (including curing agent and solvent ratio) of the first resin adhesive layer, the second resin adhesive layer, and the thermally conductive adhesive layer is completely consistent with that of Example 1; the graded ratio of thermally conductive filler (Al2O3) in the thermally conductive adhesive layer is adjusted as follows: 7.8g for 1-10μm specification, 17.55g for 10-30μm specification, and 7.8g for 30-50μm specification; so that the total filling amount of thermally conductive filler is maintained at 85% of the resin volume in the thermally conductive adhesive layer; the thickness of the first resin adhesive layer and the second resin adhesive layer is 6μm.
[0035] 4.2 Preparation process Except for the thermally conductive filler ratio, the other process parameters (stirring time, drying / pre-curing conditions, hot pressing parameters, etc.) were exactly the same as in Example 1. The thickness of the thermally conductive adhesive layer after drying was measured to be 163 μm.
[0036] 4.3 Performance Test Results and Analysis Thermal conductivity: 6.7 W / (m·K) (13.6% improvement over Example 1, 8.1% improvement over Example 3); Copper foil peel strength: 1.2 N / mm (14.3% lower than Example 1, but still maintaining a high level of adhesion); Conclusion: The additional coating of the adhesive layer can significantly improve the adhesion of aluminum-based copper clad laminates. At the same time, with the adhesive layer thickness being consistent, increasing the proportion of thermally conductive filler can further improve the thermal conductivity, and the decrease in adhesion can be controlled. This is suitable for scenarios with higher requirements for thermal conductivity.
[0037] The core parameters and performance of each embodiment are compared in Table 1 below. Table 1 The embodiments may also be the following embodiments. Example 5 A method for preparing a high thermal conductivity aluminum-based copper-clad laminate. 1.1 Raw material formulation The raw materials for the first and second resin adhesive layers, by weight, are: 0.2 parts epoxy resin, 1.5 parts MEK solvent, and 0.03 parts N-methylimidazole curing agent; The raw materials for the thermally conductive adhesive layer, by weight, are: 5.2 parts epoxy resin; 4.8 parts phenolic resin; 0.3 parts N-methylimidazole curing agent; 4 parts MEK solvent; and Al2O3 thermally conductive filler, in graded proportions: 3.9 parts for 1~10μm specification, 15.6 parts for 10~30μm specification, and 7.8 parts for 30~50μm specification. Note: The total filling amount of thermally conductive filler is 70% of the resin volume in the thermally conductive adhesive layer. The density of epoxy resin and phenolic resin is calculated as 1 g / cm³. 3 The density of Al2O3 is calculated to be 3.9 g / cm³. 3 calculate.
[0038] The content represented by each component in the first resin adhesive layer, the second resin adhesive layer, and the thermally conductive adhesive layer may differ.
[0039] 1.2 Preparation steps Step A: Preparation and pre-curing of the first resin adhesive layer All raw materials except the curing agent in the first resin adhesive layer raw material are added to a mixing device and stirred for 25 minutes until homogeneous; after adding the curing agent, stirring is continued for 28 minutes to obtain the coating liquid of the first resin adhesive layer. The coating liquid of the first resin adhesive layer was applied to the surface of the aluminum plate substrate by using a wire rod, and dried and pre-cured at 120°C for 5 minutes to obtain a thickness of 5μm for the first resin adhesive layer. Step B: Coating and drying of thermally conductive adhesive layer Add all the raw materials of the thermally conductive adhesive layer except the curing agent to the mixing equipment and stir for 30 minutes until uniform; after adding the curing agent, continue stirring for 30 minutes to obtain the coating liquid of the thermally conductive adhesive layer; The coating liquid of the thermally conductive adhesive layer is coated on the surface of the first resin adhesive layer prepared in step A. It is first dried at 120°C for 9 min, and then heated to 150°C and held for 5 min. The thickness of the resulting thermally conductive adhesive layer is 150 μm. Step C: Application of the second resin adhesive layer Using the same raw material formulation and coating and pre-curing process as in step A, a second resin adhesive layer is coated on the surface of the thermally conductive adhesive layer to obtain a second resin adhesive layer with a thickness of 5 μm. Step D: Hot pressing composite molding Copper foil is covered on the other side of the second resin adhesive layer (ensuring the roughened side of the copper foil faces down), and hot-pressed at 90~170℃ and 10MPa for 240min (heating rate 2℃ / min). After cooling, the finished aluminum-based copper-clad laminate is obtained.
[0040] Example 6 A method for preparing a high thermal conductivity aluminum-based copper-clad laminate. 1.1 Raw material formulation The raw materials for the first and second resin adhesive layers, by weight, are: 0.5 parts phenolic resin, 1.8 parts MEK solvent, and 0.03 parts N-methylimidazole curing agent; The raw materials of the thermally conductive adhesive layer, by weight, are: 6 parts epoxy resin, 4 parts phenolic resin; 1 part N-methylimidazole curing agent; 4.5 g MEK solvent; and Al2O3 thermally conductive filler, in graded proportions: 3.9 parts for 1~10μm specification, 15.6 parts for 10~30μm specification, and 7.8 parts for 30~50μm specification. Note: The total filling amount of thermally conductive filler is 70% of the resin volume in the thermally conductive adhesive layer.
[0041] The content represented by each component in the first resin adhesive layer, the second resin adhesive layer, and the thermally conductive adhesive layer may differ.
[0042] 1.2 Preparation steps Step A: Preparation and pre-curing of the first resin adhesive layer All raw materials except the curing agent in the first resin adhesive layer raw material are added to a mixing device and stirred for 35 minutes until homogeneous; after adding the curing agent, stirring is continued for 32 minutes to obtain the coating liquid of the first resin adhesive layer. The coating liquid of the first resin adhesive layer was applied to the surface of the aluminum plate substrate by using a wire rod, and dried and pre-cured at 120°C for 5 minutes to obtain a thickness of 10 μm for the first resin adhesive layer. Step B: Coating and drying of thermally conductive adhesive layer Add all raw materials except the curing agent to the mixing equipment and stir for 35 minutes until homogeneous; after adding the curing agent, continue stirring for 32 minutes to obtain the coating liquid of the thermally conductive adhesive layer; The coating liquid of the thermally conductive adhesive layer is coated on the surface of the first resin adhesive layer prepared in step A. It is first dried at 120°C for 11 min, and then heated to 150°C and held for 6 min. The thickness of the resulting thermally conductive adhesive layer is 150 μm.
[0043] Step C: Application of the second resin adhesive layer Using the same raw material formulation and coating and pre-curing process as in step A, a second resin adhesive layer is coated on the surface of the thermally conductive adhesive layer to obtain a second resin adhesive layer with a thickness of 10 μm. Step D: Hot pressing composite molding Copper foil is covered on the other side of the second resin adhesive layer (ensuring the roughened side of the copper foil faces down), and hot-pressed at 90~170℃ and 10MPa for 240min (heating rate 2℃ / min). After cooling, the finished aluminum-based copper-clad laminate is obtained.
[0044] Example 7 A method for preparing a high thermal conductivity aluminum-based copper-clad laminate. 1.1 Raw material formulation The raw materials for the first and second resin adhesive layers, by weight, are: 0.3 parts epoxy resin, 1.8 parts MEK solvent, and 0.03 parts N-methylimidazole curing agent; The raw materials for the thermally conductive adhesive layer, by weight, are: 5.8 parts epoxy resin, 4.2 parts phenolic resin; 0.8 parts N-methylimidazole curing agent; 5 parts MEK solvent; and Al2O3 thermally conductive filler, graded in the following proportions: 3.9 parts for 1~10μm specification, 15.6 parts for 10~30μm specification, and 7.8 parts for 30~50μm specification. Note: The total filling amount of thermally conductive filler is 70% of the resin volume in the thermally conductive adhesive layer.
[0045] The content represented by each component in the first resin adhesive layer, the second resin adhesive layer, and the thermally conductive adhesive layer may differ.
[0046] 1.2 Preparation steps Step A: Preparation and pre-curing of the first resin adhesive layer All raw materials except the curing agent in the first resin adhesive layer raw material were added to a mixing device and stirred for 33 minutes until homogeneous; after adding the curing agent, stirring was continued for 32 minutes to obtain the coating liquid of the first resin adhesive layer. The coating liquid of the first resin adhesive layer was applied to the surface of the aluminum plate substrate by using a wire rod, and dried and pre-cured at 120°C for 5 minutes to obtain a thickness of 5μm for the first resin adhesive layer. Step B: Coating and drying of thermally conductive adhesive layer Add all the raw materials of the thermally conductive adhesive layer except the curing agent to the mixing equipment and stir for 35 minutes until uniform; after adding the curing agent, continue stirring for 30 minutes to obtain the coating liquid of the thermally conductive adhesive layer; The coating liquid of the thermally conductive adhesive layer is coated on the surface of the first resin adhesive layer prepared in step A. It is first dried at 120°C for 10 min, and then heated to 150°C and held for 5 min. The thickness of the obtained thermally conductive adhesive layer is 150 μm.
[0047] Step C: Application of the second resin adhesive layer Using the same raw material formulation and coating and pre-curing process as in step A, a second resin adhesive layer is coated on the surface of the thermally conductive adhesive layer to obtain a second resin adhesive layer with a thickness of 5 μm. Step D: Hot pressing composite molding Copper foil is covered on the other side of the second resin adhesive layer (ensuring the roughened side of the copper foil faces down), and hot-pressed at 90~170℃ and 10MPa for 240min (heating rate 2℃ / min). After cooling, the finished aluminum-based copper-clad laminate is obtained.
[0048] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. It should be noted that for those skilled in the art and any person skilled in the art, any equivalent substitutions or changes made to the technical solution and inventive concept of the present invention without departing from the overall concept of the present invention, as well as any changes and improvements made, should also be considered within the scope of protection of the present invention.
Claims
1. A high thermal conductivity aluminum-based copper-clad laminate, characterized in that: The device includes an aluminum substrate, a copper foil, and a thermally conductive adhesive layer between the two. A first resin adhesive layer is provided between the aluminum substrate and the thermally conductive adhesive layer, and a second resin adhesive layer is provided between the copper foil and the thermally conductive adhesive layer. The thicknesses of the first and second resin adhesive layers are 5-10 μm, respectively. The thermally conductive filler in the thermally conductive adhesive layer accounts for approximately 70%-85% of the resin volume in the thermally conductive adhesive layer. The resin in the thermally conductive adhesive layer is epoxy resin and phenolic resin, and the resins in the first and second resin adhesive layers are at least one of epoxy resin and phenolic resin.
2. The high thermal conductivity aluminum-based copper-clad laminate according to claim 1, characterized in that: The raw materials of the resin matrix system of the thermally conductive adhesive layer include: 50-60 parts of epoxy resin, 40-50 parts of phenolic resin, and 3-10 parts of curing agent; the thermally conductive filler is at least one of alumina, boron nitride, silicon carbide, and diamond, and its particle size is 1-50 μm.
3. The high thermal conductivity aluminum-based copper-clad laminate according to claim 2, characterized in that: The thermally conductive filler has a composite particle size distribution, in which 1~10μm particles account for 12%~25%, 10~30μm particles account for 50%~60%, and 30~50μm particles account for 23%~30%.
4. The high thermal conductivity aluminum-based copper-clad laminate according to claim 1, characterized in that: The thickness of the thermally conductive adhesive layer is 130~180mm.
5. The high thermal conductivity aluminum-based copper-clad laminate according to claim 1 or 2, characterized in that: The raw materials in the first resin adhesive layer and the second resin adhesive layer respectively include 2-5 parts of resin and 0.3 parts of curing agent.
6. The method for preparing a high thermal conductivity aluminum-based copper-clad laminate according to any one of claims 1-5, characterized in that: The following steps are included: (1) Add all raw materials and solvents except curing agent to the raw materials of the first resin adhesive layer, the second resin adhesive layer and the thermally conductive adhesive layer and mix them evenly in a mixing device. Then add curing agent and continue to mix evenly to obtain coating liquids of the first resin adhesive layer, the second resin adhesive layer and the thermally conductive adhesive layer respectively. (2) A coating liquid for the first resin adhesive layer is applied to one side of the aluminum substrate and pre-cured to form the first resin adhesive layer; (3) Apply a coating liquid of thermally conductive adhesive layer to the surface of the first resin adhesive layer and pre-cur it to form a thermally conductive adhesive layer; (4) The coating liquid of the second resin adhesive layer is applied to the thermally conductive adhesive layer and then hot-pressed with the roughened copper foil; or the coating liquid of the second resin adhesive layer is directly applied to the roughened surface of the copper foil to form the second resin adhesive layer, and then pressed with the aluminum substrate that has been coated with the thermally conductive adhesive layer.
7. The method for preparing a high thermal conductivity aluminum-based copper-clad laminate according to claim 6, characterized in that: The coating liquids of the first resin adhesive layer, the second resin adhesive layer, and the thermally conductive adhesive layer are applied by micro-recessed coating, slot coating, or wire rod coating. The wet film thickness is controlled to be 8~15μm, and the dry film thickness after pre-curing is 5~10μm.
8. The method for preparing a high thermal conductivity aluminum-based copper-clad laminate according to claim 6, characterized in that: The solvent is methyl ethyl ketone.
Citation Information
Patent Citations
Aluminum-based copper-clad plate with high thermal conductivity and manufacturing method thereof
CN104708869A
Preparation method and device of high-thermal-conductivity copper-clad plate
CN111823693A